Oppimisympäristöt A1-kielen opetuksen mahdollistajina vuosiluokilla 1–2 - Vahtola Tiia; Lintunen Pekka; Maijala Minna (Finland, 2022)
This article presents how teachers implement early foreign language (FL) teaching in first and second grades in Finnish primary schools. The purpose of the research was to gather information on how different kinds of learning environments are being used in FL teaching. The participants planned and conducted their own teaching development projects. Their reports of the projects were collected during spring 2020, and they also included information on how the teachers conducted remote teaching due to the COVID-19 pandemic. Altogether 10 reports written by general class teachers and FL teachers were analyzed using qualitative content analysis with a theory-oriented framework. The results show that teachers implement functional language teaching methods in various learning environments. Use of digital learning materials has become more essential during the remote teaching period. The study provides valuable insights into the use of learning environments in early foreign language teaching in Finland.